Determinant of Customer Purchase Intention Towards Residential Properties Market in Penang - Mohd Amirul Hafidz, Ahmat (2011)
This study purposed to determine the purchase intention towards residential properties market in Penang. A field survey of visiting customer to properties companies in Penang was conducted to determine the influence factors of price, product, place/location and promotion on customer purchasing intention of residential properties in Penang. A total of 200 questionnaires have been distributed to the people who have visited at the properties companies in Penang through convenience sampling. 187 were obtained and 173 are usable for the research. Correlation analysis showed that “price” has the most significant factors followed by “product”, “promotion” and “place”. Conversely, regression analysis indicated that price is the major factors of purchasing intention of Penang people and properties developers should focus more on pricing rather other factors of marketing mix in order for developers to sell their product. Recommendation for future research was also put forward.